CuGaS2–ZnS p–n nanoheterostructures: a promising visible light photo-catalyst for water-splitting hydrogen production. Issue 37 (8th September 2016) - Zhao, Mingshi; Huang, Feng; Lin, Hang; Zhou, Jiangcong; Xu, Ju; Wu, Qingping; Wang, Yuansheng
Abstract : In this work, novel CuGaS2 –ZnS p–n type semiconductor nanoheterostructures were synthesized by a solution route, and demonstrated experimentally to be a very promising visible light active photo-catalyst for water-splitting hydrogen production. Abstract : In this work, novel CuGaS2 –ZnS p–n type semiconductor nanoheterostructures were synthesized by a solution route, and demonstrated experimentally to be a very promising visible light active photo-catalyst for water-splitting hydrogen production. The construction of CuGaS2 –ZnS heterostructures follows a multi-step strategy, employing Cu1.94 S nanocrystals first as catalytic assistants for the hetero-growth of ZnS on their surfaces, and then as sacrificial seeds for the formation of CuGaS2 . Excitingly, attributed to the efficient charge separation introduced by the p–n heterojunctions, the hydrogen production ability of the CuGaS2 –ZnS nanoheterostructures under visible light irradiation is 15 times higher than that of the CuGaS2 component, and comparable to that of the CdS nanophase which is currently regarded as one of the most active visible photo-catalysts for hydrogen generation.